Early achievements in cardiovascular care as reflected in the Journal of Internal Medicine. (December 2013) - Rydén, L.
Abstract: This review mirrors progress in cardiovascular medicine as reflected by scientific contributions published in the Journal of Internal Medicine (from 1989), Acta Medica Scandinavica (from 1919 until 1989) and Nordiskt Medicinskt Arkiv (before 1919). A total of 149 articles were identified within this field since the first, published work in this field 1877–1970. The latter year was set as and end for the review since this was the year the first contribution by the author of this review was published in the journal. To cope with the large number individual publications related to different aspects of cardiovascular medicine were grouped together into fields in which Scandinavian contributions were pioneering or for other reasons of particular interest. These articles were briefly summarized together with some information of the author(s) and the contributions were put into the perspective of subsequent importance and/or scientific and clinical development. Among topics with insightful contributions published in the journal are electrophysiology, diagnostic techniques including standardization, endurance exercise and the heart, electrocardiography, myocardial infarction, atrio‐ventricular block and cardiac pacing. Some of these early contributions were indeed, considering the methods available at the time for the investigations impressive and many predictions truly insightful and imaginative. Other contributions may, at least by the present day reader, seem somewhat odd.